PENILAIAN MULTIDIMENSIONAL KEPRIBADIAN PADA PENYANDANG EPILEPSI - Irina Kemala Nasution, Rusli Dhanu, Hasan Sjahrir (NEURONA, 2012)
INTRODUCTION WHEN EPILEPSY AFFECTS FOR LONG PERIODS IT MAY NOTICE CHANGES IN BEHAVIOR AND FEELINGS THE QUESTION OF PERSONALITY DISORDERS ASSOCIATED WITH EPILEPSY HAS ALONG HISTORY AND REMAINS CONTROVERSIAL SOME AUTHORS FIND A GREATER INCIDENCE OF BEHAVIORAL DISORDERS IN PATIENTS WITH EPILEPSY THAN IN GENERAL POPULATION